Development of an ELA-DRA gene typing method based on pyrosequencing technology - Diaz, Silvina (2008)
The polymorphism of equine lymphocyte antigen (ELA) class II DRA gene had been detected by polymerase chain reaction-single-strand conformational polymorphism (PCR-SSCP) and reference strand-mediated conformation analysis. These methodologies allowed to identify 11 ELA-DRA exon 2 sequences, three of which are widely distributed among domestic horse breeds. Herein, we describe the development of a pyrosequencing-based method applicable to ELA-DRA typing, by screening samples from eight different horse breeds previously typed by PCR-SSCP. This sequence-based method would be useful in high-throughput genotyping of major histocompatibility complex genes in horses and other animal species, making this system interesting as a rapid screening method for animal genotyping of immune-related genes.